Fleksibilitas Tempat Kerja dan Komunikasi Internal dengan Mediasi Kreativitas Karyawan terhadap Efektivitas Pemasaran Media di dalam UMKM - Rahmatullah, Agung Nugraha; Sukemi, Sukemi (Awatara Publisher, 2026)
This study investigates the effects of workplace flexibility and internal communication on marketing effectiveness through employee creativity in micro, small, and medium-sized enterprises (MSMEs). Using a quantitative approach, data were collected from 370 employees of MSMEs in Purwakarta, Indonesia, who are actively involved in marketing-related activities. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was applied to test the proposed relationships. The results show that workplace flexibility has a significant positive effect on employee creativity, and internal communication also significantly enhances creative behavior. Employee creativity is found to positively influence marketing effectiveness, indicating that creative engagement is essential for achieving effective marketing outcomes. Furthermore, employee creativity mediates the relationships between workplace flexibility and marketing effectiveness, as well as between internal communication and marketing effectiveness. These findings suggest that organizational practices shape market performance through behavioral mechanisms. The study contributes to creativity and marketing literature by integrating internal organizational factors with external performance outcomes. Practically, the results provide guidance for MSME managers in designing flexible and communicative work environments to strengthen creative capacity and improve marketing effectiveness.